2015
DOI: 10.1063/1.4922652
|View full text |Cite
|
Sign up to set email alerts
|

CO2 binding in the (quinoline-CO2)− anionic complex

Abstract: We have studied the (quinoline-CO2)(-) anionic complex by a combination of mass spectrometry, anion photoelectron spectroscopy, and density functional theory calculations. The (quinoline-CO2)(-) anionic complex has much in common with previously studied (N-heterocycle-CO2)(-) anionic complexes both in terms of geometric structure and covalent bonding character. Unlike the previously studied N-heterocycles, however, quinoline has a positive electron affinity, and this provided a pathway for determining the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…So the CO 2 •– anion is metastable with a short lifetime of ∼90 ms. , As a result, despite being highly reactive, the direct use of CO 2 •– for further CO 2 fixation has been difficult and scarce . Instead of directly using electrons, another strategy is to use anions or partial negative charges to attack the carbon atom on CO 2 , yielding stable products with carboxylic groups. …”
Section: Introductionmentioning
confidence: 99%
“…So the CO 2 •– anion is metastable with a short lifetime of ∼90 ms. , As a result, despite being highly reactive, the direct use of CO 2 •– for further CO 2 fixation has been difficult and scarce . Instead of directly using electrons, another strategy is to use anions or partial negative charges to attack the carbon atom on CO 2 , yielding stable products with carboxylic groups. …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, He and co-workers have proved that the amino acid salts are capable of capturing 1 equiv of CO 2 through the insertion of CO 2 into N–H bond . Bowen et al found that CO 2 can bind to the quinoline N atom to form the quinoline-CO 2 anionic complex . In addition, previously reported catalysts and catalytic systems showed that NHCs (N-heterocyclic carbenes) can react with CO 2 to form NHC-CO 2 adducts. , These recent advances prompted our interest in the design of effective multifunctional catalysts which allow the simultaneous activation of CO 2 and the epoxide.…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectron spectroscopy provided detailed information on CO2 binding in the quinoline-CO2 •− complex [37] as well as anionic coinage metal complexes [38]. Coadsorption of CO2 and pyridine to Coled to strong binding of both ligands to the central metal atom [39].…”
Section: Introductionmentioning
confidence: 99%